MOTHER'S VIOLENT BEHAVIOR IN CHILDREN - Widiningsih, Yuli (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
This study aims to get a picture of the forms of violent behavior perpetrated by mothers against children in poor communities. The research respondents classified as poor were obtained by the category of families who received the Program Keluarga Harapan (PKH) assistance, totaling 140 people. Measuring instruments using a scale of violence against children are arranged based on forms of violence against children. Based on demographic data, the following description of respondents was obtained: 93% were married, 96% were housewives, 52% were elementary school graduates, 66% were husband's work as laborers. While the results of the analysis of items on the scale of violence against children obtained data that the form of violent behavior of mothers against children includes: hitting children with hands or with light objects, pinching, slapping, threatening not to give money, calling children by nicknames, comparing children with other children, and say deaf to children. This form of violence is perpetrated by mothers against children with a frequency of 17% rarely, 69% sometimes and 14% often.